Genesis of the Essential Content of the Hotel Service as an Object of Consumer-Oriented Marketing - Khayrullaeva Nilufarbeim Nematilloyevna; Narzullayeva Gulchekhra Salimovna; Tairova Masuma Muxammedovna (Research Parks Publishers, 2021)
In the article development of theoretical foundations and methodological provisions for the formation of an integrated approach to the development of a marketing strategy for hotel services, the use of marketing mix tools to ensure the effectiveness of marketing communications with hotel consumers services.